Pengembangan Media Tangram Materi Komposisi Bangun Datar untuk Siswa Kelas IV Sekolah Dasar - Cindy, Vista; Sartika, R. Rami (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2025)
This study aims to develop a geometry learning media in the form of Tangram on the material of flat shape composition for grade IV elementary school students. The development method used is Research and Development (R&D) with the ADDIE model. The results of the development in the form of Tangram media have been tested on 22 students of SDN 113 Pekanbaru. The results of observations and questionnaires showed that students showed enthusiasm and good abilities in using Tangram media, and gave a positive assessment of the effectiveness of the media in learning flat shape composition. This study shows that Tangram media can be effectively used in improving the understanding of geometry concepts in elementary school students.